Computer Screen Use Detection Using Smart Eyeglasses - Wahl, Florian; Kasbauer, Jakob; Amft, Oliver (Frontiers in ICT, 2017)
Screen use can influence the circadian phase and cause eye strain. Smart eyeglasses with an integrated colour light sensor can detect screen use. We present a screen use detection approach based on a light sensor embedded into the bridge of smart eyeglasses. By calculating the light intensity at the user’s eyes for different screens and content types we found only computer screens to have significant impact on the circadian phase. Our screen use detection is based on ratios between colour channels and used a linear support vector machine to detect screen use. We validated our detection approach in three studies. A Test bench was built to detect screen use under different ambient light sources and intensities in a controlled environment. In a Lab study, we evaluated recognition performance for different ambient light intensities. Using participant-independent models we achieved a ROC AUC above 0.9 for ambient light intensities below 200 lux. In a study of typical ADLs screen use was detected with an average ROC AUC of 0.83 assuming screen use for 30 % of the time.